Low-intensity pulsed ultrasound enhances bone formation around miniscrew implants. Issue 6 (June 2015) - Ganzorig, Khaliunaa; Kuroda, Shingo; Maeda, Yuichi; Mansjur, Karima; Sato, Minami; Nagata, Kumiko; Tanaka, Eiji
Highlights LIPUS increased the bone-implant contact around MSIs. LIPUS induced significant upregulation of ALP in MC3T3-E1 cells at day 3. LIPUS enhanced bone formation around MSIs. LIPUS might enhance the initial stability after both Ti and SS MSIs implantation.